Study of land potential based on soil characteristics using interpolation and scoring methods for non agricultural uses: a case study in Wonosalam, Jombang District, East Java - Siswanto, Siswanto; Sasongko, Purnomo Edi (Universitas Trunojoyo Madura, 2024)
The state asset land managed by UPN